2016
DOI: 10.1007/s00203-016-1304-7
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of rhizobacterial communities in pepper greenhouses and examination of the effects of salt accumulation under different cropping systems

Abstract: This study compared rhizobacterial communities in pepper greenhouses under a paddy-upland (rice-pepper) rotational system (PURS) and a monoculture repeated cropping system (RCS) and examined adverse effects of high salinity on soil properties. The following soil properties were analyzed: electrical conductivity (EC), pH, concentration of four cations (Na, Ca, Mg, and K), total nitrogen, and organic matter content. Rhizobacterial communities were analyzed using culture-based and culture-independent (pyrosequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 39 publications
2
8
0
Order By: Relevance
“…The studies illustrated that highly diverse cropping systems were less affected by soil-borne pathogens than the plant mono-fields or low-diversity fields. This is consistent with the results of crop diseases (Figure 3), and highlighted that FC system not only increased soil bacterial relative abundance but also decreased soil borne pathogens [25][26][27][28].…”
Section: 11benefit Of Plants As Results Of Changes In Soil Microbiasupporting
confidence: 91%
See 1 more Smart Citation
“…The studies illustrated that highly diverse cropping systems were less affected by soil-borne pathogens than the plant mono-fields or low-diversity fields. This is consistent with the results of crop diseases (Figure 3), and highlighted that FC system not only increased soil bacterial relative abundance but also decreased soil borne pathogens [25][26][27][28].…”
Section: 11benefit Of Plants As Results Of Changes In Soil Microbiasupporting
confidence: 91%
“…To further understanding the correlation of microbial diversity and environmental factors such as the content of N, P, K, and the activities of PPO, SC, UE and CAT, the Spearman correlation analysis was carried out as reported previously [25]. https://doi.org /10.37358/Rev.…”
Section: 9spearman Correlation Analysis Of Microbial Diversity Andmentioning
confidence: 99%
“…Enterobacteriaceae seem to have shifted from the RAS to the roots in the presence of saline stress. Similar results on the effects of NaCl in the rhizosphere of various agricultural crops (Li et al, 2016;Nie et al, 2016;Hahm et al, 2017;Ibekwe et al, 2017) and on natural halophytes (Liu et al, 2016;Yang et al, 2016) have been previously reported. However, the length of 16S sequences obtained with current high-throughput sequencing techniques is relatively short, and does not allow us to describe OTUs at the species level, and since within the same bacterial genus, phytobeneficial bacteria and pthytopathogens can co-exist, we can hardly claim that the plant, under certain stress conditions, will select specifically beneficial microbiota.…”
Section: Discussionsupporting
confidence: 87%
“…Three PGPR strains that possess plant growth-promoting attributes, like phosphate solubilization and the production of IAA, siderophore, and ACC deaminase, were previously isolated from the from the rhizospheric soil of pepper plants growing under saline conditions in Mir-Yang, Republic of Korea [18]. Cultures of the three PGPR strains were grown in 500 ml of tryptic soy broth at 30°C.…”
Section: Pgpr Strains and Experimental Designmentioning
confidence: 99%
“…In the present study, we used three PGPR strains that were previously isolated from the rhizosphere of pepper plants grown under highly saline conditions [18]. These isolates were M. oleivorans KNUC7074, B. iodinum KNUC7183, and R. massiliae KNUC7586.…”
Section: Characterization Of Pgpr Strainsmentioning
confidence: 99%